2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.bertschinger
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Change: TEAM-UP and Beyond

Abstract: The AIP TEAM-UP report identifies the structural and systemic causes explaining why African Americans have not experienced the growth in bachelor's degrees in physics the way they have in other fields or as other minority groups have experienced in physics over the past two decades. Solving these problems requires changing not only the way physicists train students, but how they think about training students. Research on change in higher education suggests the need for physicists and astronomers to recognize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, only about half of these respondents indicated that department climate and creating an inclusive learning environment was an issue, suggesting a gap between perceived problems versus the change efforts needed to address systemic and cultural barriers. A written guide has limited ability to address these gaps; the deeper learning and broader stakeholder engagement needed for second-order change cannot be addressed with only first-order methods [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only about half of these respondents indicated that department climate and creating an inclusive learning environment was an issue, suggesting a gap between perceived problems versus the change efforts needed to address systemic and cultural barriers. A written guide has limited ability to address these gaps; the deeper learning and broader stakeholder engagement needed for second-order change cannot be addressed with only first-order methods [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, [10] critiqued change efforts that focus on individual faculty practices as "overly simplistic" and unable to create widespread sustained change. Separately, [11] summarized the TEAM-UP report's [12] argument that cultural change is necessary to address why the number of physics bachelor's degrees has more than doubled for all federally reported racial and ethnic groups except Black or African Americans (as well as American Indian and Alaskan Natives). Because the physics community needs to grapple with its own culture, value, and norms, using only first-order methods is likely to end in failure [11].…”
Section: Literature Reviewmentioning
confidence: 99%